High-toughness composite cable and preparation method thereof
By generating zinc oxide in situ on carbon nanotubes and organically modifying, and melt extrusion combined with GMA, styrene and PP, the interfacial compatibility problem of polypropylene composite materials is solved, and its bending strength and wear resistance are significantly improved.
Patent Information
- Application Number
- CN202510144708.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-02-10
AI Technical Summary
Polypropylene composite materials have poor mechanical properties due to interface compatibility problems in the field of cables.
By generating zinc oxide in situ on carbon nanotubes, its dispersion is improved, and modified by silane coupling agent, grafting is combined with 3-methoxy-4-hydroxycinnamic acid and thiol succinic acid to form grafts, forming organic coated preformed particles, and finally melt-extruded with GMA, styrene and PP, enhancing the dispersion and compatibility of the inorganic filler in the polypropylene system.
The bending strength and wear resistance of polypropylene cable materials are significantly improved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables and relates to a high-toughness composite cable and a preparation method thereof. Background Art
[0002] Polypropylene composites have been widely used in the field of cable materials due to their excellent impact resistance and chemical corrosion resistance. By introducing fillers such as inorganic fibers, natural fibers and hollow glass beads into the polypropylene matrix, its heat resistance and low-temperature impact properties can be significantly improved. However, as a non-polar material without functional groups, polypropylene has a large interface compatibility problem with polar fillers, resulting in unsatisfactory mechanical properties of the composites. To solve this problem, two strategies are usually adopted: one is to modify the surface of the filler, such as through chemical treatment or adding interfacial compatibilizers to reduce the interfacial energy and enhance the interfacial interaction; the other is to improve the interfacial compatibility between the filler and the polypropylene matrix by optimizing the preparation process of the composite material, thereby improving the overall mechanical properties of the material. Summary of the invention
[0003] The object of the present invention is to provide a high-toughness composite cable and a preparation method thereof. The present invention generates zinc oxide in situ on carbon nanotubes to improve the dispersibility of the two, then modifies them with a silane coupling agent, combines 3-methoxy-4-hydroxycinnamic acid with prefabricated particles to form grafts with mercaptosuccinic acid to form organic coated prefabricated particles, and finally melt-extrudes with GMA, styrene and PP to increase the dispersibility and compatibility of inorganic fillers compounded with carbon nanotubes / zinc oxide in a polypropylene overall system, thereby significantly improving the bending strength and wear resistance of polypropylene cable materials.
[0004] The purpose of the present invention can be achieved through the following technical solutions: A high-toughness composite cable comprises a cable body and a sheath layer, wherein the sheath layer is arranged on the cable body, and is characterized in that the sheath layer comprises the following components in parts by weight: Polypropylene 75-85 parts 20-23 parts of organic modified filler 7-8 parts of additives; As a preferred technical solution of the present invention, the cable body includes a plurality of copper conductive cores and a metal shielding layer wrapping the plurality of copper conductive cores.
[0005] As a preferred technical solution of the present invention, the auxiliary agent is formed by mixing a lubricant, an antioxidant and an anti-ultraviolet agent in a mass ratio of 5:3.0-3.2:1.8-2.2.
[0006] As a preferred technical solution of the present invention, the lubricant is one or both of oxidized polyethylene wax and montan wax; the antioxidant is one or more of antioxidant 168, antioxidant 1010 and antioxidant 1076; and the anti-ultraviolet agent is UV-9.
[0007] As a preferred technical solution of the present invention, the method for preparing the organic modified filler comprises the following steps: Step 1: After mixing carbon nanotubes, chloride salt and deionized water, slowly add sodium hydroxide aqueous solution and stir to mix, vacuum filter, wash to neutrality, place in an oven for drying, and calcine to obtain composite powder; Step 2: After mixing anhydrous ethanol and a catalyst, adding a silane coupling agent and a composite powder, stirring at a constant temperature, centrifuging, washing, and drying in an oven to obtain prefabricated particles; Step 3: After the reaction monomer and anhydrous ethanol are mixed, the prefabricated particles and the initiator are added and stirred, and then mercaptosuccinic acid is added and ultraviolet irradiation is performed under an inert atmosphere, and then the mixture is centrifuged, washed, and dried in an oven to obtain modified particles; Step 4: After the modified particles, styrene, crosslinking agent, PP and GMA are kneaded, they are placed in an extruder for melt extrusion, and pelletized to obtain an organic modified filler.
[0008] As a preferred technical solution of the present invention, in step one, the stirring and mixing is stirring at a speed of 500-600 r / min for 3-4 hours; the cleaning is cleaning with deionized water; the drying is drying at a temperature of 70-80°C to constant weight; and the calcination is calcining at a temperature of 230°C for 3-4 hours.
[0009] As a preferred technical solution of the present invention, in step 1, the mass ratio of the carbon nanotubes, chloride salt, deionized water and sodium hydroxide aqueous solution is 1.8-2.1:1.0-1.2:18-20:15-16; the chloride salt is prepared by mixing zinc chloride and sodium chloride in a mass ratio of 10-11:1; and the mass fraction of the sodium hydroxide aqueous solution is 20%.
[0010] As a preferred technical solution of the present invention, in step 2, the mass ratio of the composite powder, silane coupling agent, catalyst and anhydrous ethanol is 10-14:3-4:0.02-0.03:40-50; the silane coupling agent is triethoxyvinylsilane; and the catalyst is dibutyltin dilaurate.
[0011] As a preferred technical solution of the present invention, in step 2, the constant temperature stirring is stirring at 50-60°C for 10-12h; the cleaning is cleaning three times with anhydrous ethanol; and the drying is drying at 70-80°C to constant weight.
[0012] As a preferred technical solution of the present invention, in step three, the mass ratio of the reaction monomer, prefabricated particles, mercaptosuccinic acid, anhydrous ethanol and initiator is 1.0-1.4:12-14:2.6-3.0:50-60:0.10-0.12; the reaction monomer is 3-methoxy-4-hydroxycinnamic acid; the initiator is benzoin dimethyl ether; the stirring and mixing is stirring at a speed of 600-800r / min for 4-5h; the ultraviolet irradiation treatment is ultraviolet irradiation at a speed of 150-180r / min and a wavelength of 365nm for 20-24h; the inert atmosphere is a nitrogen atmosphere; the cleaning is cleaning three times with anhydrous ethanol; and the drying is drying at a temperature of 80°C to constant weight.
[0013] As a preferred technical solution of the present invention, in step 4, the mass ratio of the modified particles, styrene, cross-linking agent, PP and GMA is 14-16: 1.6-1.8: 0.26-0.30: 20-24: 3.2-3.8; the melt extrusion is melt extrusion at a speed of 50 rpm and a temperature of 190°C for 5 min; the cross-linking agent is dicumyl peroxide; the GMA is glycidyl methacrylate; and the PP is polypropylene.
[0014] The invention discloses a method for preparing a high-toughness composite cable, which comprises the following steps: mixing polypropylene, organic modified fillers and additives in an internal mixer, melting and extruding the mixture at a temperature of 190-200°C to obtain a mixture, and melting and extruding the mixture on the surface of a cable body to obtain a composite cable.
[0015] Beneficial effects of the present invention: The invention generates zinc oxide in situ on carbon nanotubes to improve the dispersibility of the two, then modifies them through a silane coupling agent, combines 3-methoxy-4-hydroxycinnamic acid with prefabricated particles to form grafts with mercaptosuccinic acid to form organic coated prefabricated particles, and finally melt-extrudes with GMA, styrene and PP to increase the dispersibility and compatibility of inorganic fillers compounded with carbon nanotubes / zinc oxide in the overall polypropylene system, thereby significantly improving the bending strength and wear resistance of polypropylene cable materials. DETAILED DESCRIPTION
[0016] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments. Example
[0017] A high-toughness composite cable comprises a cable body and a sheath layer, wherein the sheath layer is arranged on the cable body, and the sheath layer comprises the following components in parts by weight: Polypropylene 75 parts 20 parts of organic modified filler 7 parts of additives; The auxiliary agent is formed by mixing a lubricant, an antioxidant and an anti-ultraviolet agent in a mass ratio of 5:3.0:1.8; the lubricant is oxidized polyethylene wax; the antioxidant is antioxidant 1010; and the anti-ultraviolet agent is UV-9.
[0018] The preparation method of the organic modified filler comprises the following steps: Step 1: After mixing carbon nanotubes, chloride salt and deionized water, slowly add sodium hydroxide aqueous solution and stir at a speed of 500r / min for 3h, vacuum filter, wash with deionized water until neutral, place in an oven, dry at 70°C to constant weight, and calcine at 230°C for 3h to obtain composite powder; the mass ratio of the carbon nanotubes, chloride salt, deionized water and sodium hydroxide aqueous solution is 1.8:1.0:18:15; the chloride salt is prepared by mixing zinc chloride and sodium chloride in a mass ratio of 10:1; the mass fraction of the sodium hydroxide aqueous solution is 20%; Step 2: After mixing anhydrous ethanol and a catalyst, a silane coupling agent and a composite powder are added, and the mixture is stirred at 50° C. for 10 hours, and then the solid is centrifuged and washed three times with anhydrous ethanol, and then placed in an oven, and dried at 70° C. to constant weight to obtain prefabricated particles; the mass ratio of the composite powder, the silane coupling agent, the catalyst and anhydrous ethanol is 10:3:0.02:40; the silane coupling agent is triethoxyvinylsilane; and the catalyst is dibutyltin dilaurate; Step 3: After the reaction monomer and anhydrous ethanol are mixed, the prefabricated particles and the initiator are added and stirred at a speed of 600 r / min for 4 hours, and then, in a nitrogen atmosphere, mercaptosuccinic acid is added and irradiated with ultraviolet light at a speed of 150 r / min and a wavelength of 365 nm for 20 hours, and the solid is centrifuged and washed three times with anhydrous ethanol, placed in an oven, and dried at a temperature of 80° C. to constant weight to obtain modified particles; the mass ratio of the reaction monomer, the prefabricated particles, mercaptosuccinic acid, anhydrous ethanol and the initiator is 1.0:12:2.6:50:0.10; the reaction monomer is 3-methoxy-4-hydroxycinnamic acid; the initiator is benzoin dimethyl ether; Step 4: After kneading the modified particles, styrene, cross-linking agent, PP and GMA, place them in an extruder, melt-extrude at a speed of 50 rpm and a temperature of 190°C for 5 min, and then pelletize to obtain an organic modified filler; the mass ratio of the modified particles, styrene, cross-linking agent, PP and GMA is 14:1.6:0.26:20:3.2; the cross-linking agent is diisopropylbenzene peroxide.
[0019] A preparation method of a high-toughness composite cable comprises the following steps: mixing polypropylene, organic modified filler and additives in an internal mixer, melt-extruding at 190°C to obtain a mixture, and melt-extruding the mixture on the surface of a cable body to obtain the cable. Example
[0020] A high-toughness composite cable comprises a cable body and a sheath layer, wherein the sheath layer is arranged on the cable body, and the sheath layer comprises the following components in parts by weight: Polypropylene 80 parts 22 parts of organic modified filler 7.5 parts of additives; The auxiliary agent is formed by mixing a lubricant, an antioxidant and an anti-ultraviolet agent in a mass ratio of 5:3.1:2; the lubricant is oxidized polyethylene wax; the antioxidant is antioxidant 1010; and the anti-ultraviolet agent is UV-9.
[0021] The preparation method of the organic modified filler comprises the following steps: Step 1: After mixing carbon nanotubes, chloride salt and deionized water, slowly add sodium hydroxide aqueous solution and stir at a speed of 550r / min for 3.5h, vacuum filter, wash with deionized water until neutral, place in an oven, dry at 75°C to constant weight, and calcine at 230°C for 3.5h to obtain composite powder; the mass ratio of the carbon nanotubes, chloride salt, deionized water and sodium hydroxide aqueous solution is 2:1.1:19:15.5; the chloride salt is prepared by mixing zinc chloride and sodium chloride in a mass ratio of 10.5:1; the mass fraction of the sodium hydroxide aqueous solution is 20%; Step 2: After mixing anhydrous ethanol and a catalyst, add a silane coupling agent and a composite powder, stir at a temperature of 55°C for 11 hours, centrifuge to obtain a solid, wash it three times with anhydrous ethanol, place it in an oven, and dry it at a temperature of 75°C to constant weight to obtain prefabricated particles; the mass ratio of the composite powder, the silane coupling agent, the catalyst and anhydrous ethanol is 12:3.5:0.025:45; the silane coupling agent is triethoxyvinylsilane; the catalyst is dibutyltin dilaurate; Step 3: After the reaction monomer and anhydrous ethanol are mixed, the prefabricated particles and the initiator are added and stirred at a speed of 700 r / min for 4.5 hours, and then, in a nitrogen atmosphere, mercaptosuccinic acid is added and irradiated with ultraviolet light at a speed of 165 r / min and a wavelength of 365 nm for 22 hours, and the solid is centrifuged and washed three times with anhydrous ethanol, placed in an oven, and dried at a temperature of 80° C. to constant weight to obtain modified particles; the mass ratio of the reaction monomer, the prefabricated particles, mercaptosuccinic acid, anhydrous ethanol and the initiator is 1.2:13:2.8:55:0.11; the reaction monomer is 3-methoxy-4-hydroxycinnamic acid; the initiator is benzoin dimethyl ether; Step 4: After kneading the modified particles, styrene, cross-linking agent, PP and GMA, place them in an extruder, melt-extrude at a speed of 50 rpm and a temperature of 190°C for 5 min, and then pelletize to obtain an organic modified filler; the mass ratio of the modified particles, styrene, cross-linking agent, PP and GMA is 15:1.7:0.28:22:3.5; the cross-linking agent is diisopropylbenzene peroxide.
[0022] A preparation method of a high-toughness composite cable comprises the following steps: mixing polypropylene, organic modified filler and additives in an internal mixer, melt-extruding at 195°C to obtain a mixture, and melt-extruding the mixture on the surface of a cable body to obtain the composite cable. Example
[0023] A high-toughness composite cable comprises a cable body and a sheath layer, wherein the sheath layer is arranged on the cable body, and the sheath layer comprises the following components in parts by weight: Polypropylene 85 parts 23 parts of organic modified filler 8 parts of additives; The auxiliary agent is formed by mixing a lubricant, an antioxidant and an anti-ultraviolet agent in a mass ratio of 5:3.2:2.2; the lubricant is oxidized polyethylene wax; the antioxidant is antioxidant 1010; and the anti-ultraviolet agent is UV-9.
[0024] The preparation method of the organic modified filler comprises the following steps: Step 1: After mixing carbon nanotubes, chloride salt and deionized water, slowly add sodium hydroxide aqueous solution and stir at 600r / min for 4h, vacuum filter, wash with deionized water until neutral, place in an oven, dry at 80°C to constant weight, and calcine at 230°C for 4h to obtain composite powder; the mass ratio of the carbon nanotubes, chloride salt, deionized water and sodium hydroxide aqueous solution is 2.1:1.2:20:16; the chloride salt is prepared by mixing zinc chloride and sodium chloride in a mass ratio of 11:1; the mass fraction of the sodium hydroxide aqueous solution is 20%; Step 2: After mixing anhydrous ethanol and a catalyst, add a silane coupling agent and a composite powder, stir at 60°C for 12 hours, centrifuge to obtain a solid, wash it three times with anhydrous ethanol, place it in an oven, and dry it at 80°C to constant weight to obtain prefabricated particles; the mass ratio of the composite powder, silane coupling agent, catalyst and anhydrous ethanol is 14:4:0.03:50; the silane coupling agent is triethoxyvinylsilane; the catalyst is dibutyltin dilaurate; Step 3: After the reaction monomer and anhydrous ethanol are mixed, the prefabricated particles and the initiator are added and stirred at a speed of 800 r / min for 5 hours, and then, in a nitrogen atmosphere, mercaptosuccinic acid is added and irradiated with ultraviolet light at a speed of 180 r / min and a wavelength of 365 nm for 24 hours, and the solid is centrifuged and washed three times with anhydrous ethanol, placed in an oven, and dried at a temperature of 80° C. to constant weight to obtain modified particles; the mass ratio of the reaction monomer, the prefabricated particles, mercaptosuccinic acid, anhydrous ethanol and the initiator is 1.4:14:3.0:60:0.12; the reaction monomer is 3-methoxy-4-hydroxycinnamic acid; the initiator is benzoin dimethyl ether; Step 4: After kneading the modified particles, styrene, cross-linking agent, PP and GMA, place them in an extruder, melt-extrude at a speed of 50 rpm and a temperature of 190°C for 5 min, and then pelletize to obtain an organic modified filler; the mass ratio of the modified particles, styrene, cross-linking agent, PP and GMA is 16:1.8:0.30:24:3.8; the cross-linking agent is diisopropylbenzene peroxide.
[0025] A preparation method of a high-toughness composite cable comprises the following steps: mixing polypropylene, organic modified filler and additives in an internal mixer, melting and extruding at 200°C to obtain a mixture, and melting and extruding the mixture on the surface of a cable body to obtain the composite cable.
[0026] Comparative Example 1 Compared with Example 3, the difference in Comparative Example 1 is that zinc chloride is not added in step 1, and the other components, preparation steps and parameters are the same.
[0027] Comparative Example 2 Compared with Example 3, the difference in Comparative Example 2 is that no silane coupling agent is used in step 2, and the other components, preparation steps and parameters are the same.
[0028] Comparative Example 3 Compared with Example 3, the difference in Comparative Example 3 is that 3-methoxy-4-hydroxycinnamic acid is not used in step 3, and the other components, preparation steps and parameters are the same.
[0029] Comparative Example 4 Compared with Example 3, the difference in Comparative Example 4 is that mercaptosuccinic acid is not used in step 3, and the other components, preparation steps and parameters are the same.
[0030] Comparative Example 5 Compared with Example 3, the difference in Comparative Example 5 is that styrene is not used in step 4, and the other components, preparation steps and parameters are the same.
[0031] Comparative Example 6 Compared with Example 3, the difference in Comparative Example 6 is that GMA is not used in step 4, and the other components, preparation steps and parameters are the same.
[0032] The mixtures prepared in Examples 1-3 and Comparative Examples 1-6 were tested as follows, and the test results are shown in Table 1.
[0033] Bending strength test: According to GB / T 9341-2008; Wear resistance test: According to GB / T 3960-2016; Table 1 Bending strength (MPa) Wear amount (mg) Example 1 62.6 17.6 Example 2 62.9 17.1 Example 3 63.1 16.4 Comparative Example 1 42.3 33.1 Comparative Example 2 50.6 23.7 Comparative Example 3 48.1 27.3 Comparative Example 4 48.8 27.9 Comparative Example 5 52.3 21.1 Comparative Example 6 46.3 29.7 From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the cable materials prepared in Examples 1-3 have significant bending strength and wear resistance, and have excellent high toughness and wear resistance.
[0034] The invention generates zinc oxide in situ on carbon nanotubes, reduces the interaction force between the molecules, improves the dispersibility of the two, and is conducive to the subsequent organic modification. Then, the carbon nanotubes are modified by a silane coupling agent to introduce active thiol groups. Then, the 3-methoxy-4-hydroxycinnamic acid is attached to the prefabricated particles through hydrogen bonds and electrostatic adsorption between the carboxyl groups and hydroxyl groups on the 3-methoxy-4-hydroxycinnamic acid and the prefabricated particles. The thiol groups on the prefabricated particles are combined with mercaptosuccinic acid to form grafts to form organically coated prefabricated particles. The obtained modified particles are then bonded to the prefabricated particles. The GMA grafted onto the PP chain segments reacts and is fixed to the PP chain segments, and the multi-carboxyl structure of the modified particles allows GMA to react with the remaining carboxyl and phenolic hydroxyl groups on the modified particles and be indirectly grafted onto the PP chain segments. The conjugated structure of styrene and cinnamic acid groups inhibits the degradation of PP during the grafting process, and jointly improves the apparent grafting rate of GMA. GMA / PP can be used as a compatibilizer for inorganic fillers to increase their dispersibility and compatibility in the overall polypropylene system, thereby significantly improving the bending strength and wear resistance of polypropylene cable materials.
[0035] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high-toughness composite cable, comprising a cable body and a sheath layer, wherein the sheath layer is arranged on the cable body, characterized in that: The sheath layer comprises the following components in parts by weight: Polypropylene 75-85 parts 20-23 parts of organic modified filler 7-8 parts of additives; Wherein, the preparation method of the organic modified filler comprises the following steps: Step 1: After mixing carbon nanotubes, chloride salt and deionized water, slowly add sodium hydroxide aqueous solution and stir to mix, vacuum filter, wash to neutrality, place in an oven for drying, and calcine to obtain composite powder; Step 2: After mixing anhydrous ethanol and a catalyst, adding a silane coupling agent and a composite powder, stirring at a constant temperature, centrifuging, washing, and drying in an oven to obtain prefabricated particles; Step 3: After the reaction monomer and anhydrous ethanol are mixed, the prefabricated particles and the initiator are added and stirred, and then mercaptosuccinic acid is added and ultraviolet irradiation is performed under an inert atmosphere, and then the mixture is centrifuged, washed, and dried in an oven to obtain modified particles; Step 4: After the modified particles, styrene, crosslinking agent, PP and GMA are kneaded, they are placed in an extruder for melt extrusion, and pelletized to obtain an organic modified filler.
2. A high-toughness composite cable according to claim 1, characterized in that: The auxiliary agent is prepared by mixing a lubricant, an antioxidant and an anti-ultraviolet agent in a mass ratio of 5:3.0-3.2:1.8-2.
2.
3. A high-toughness composite cable according to claim 2, characterized in that: The lubricant is one or both of oxidized polyethylene wax and montan wax; the antioxidant is one or more of antioxidant 168, antioxidant 1010 and antioxidant 1076; and the anti-ultraviolet agent is UV-9.
4. A high-toughness composite cable according to claim 1, characterized in that: In step one, the stirring and mixing is performed at a speed of 500-600 r / min for 3-4 hours; the washing is performed with deionized water; the drying is performed at a temperature of 70-80° C. to constant weight; and the calcining is performed at a temperature of 230° C. for 3-4 hours.
5. The high-toughness composite cable according to claim 1, characterized in that: In step 1, the mass ratio of the carbon nanotubes, chloride salt, deionized water and sodium hydroxide aqueous solution is 1.8-2.1:1.0-1.2:18-20:15-16; the chloride salt is prepared by mixing zinc chloride and sodium chloride in a mass ratio of 10-11:1; and the mass fraction of the sodium hydroxide aqueous solution is 20%.
6. A high-toughness composite cable according to claim 1, characterized in that: In step 2, the mass ratio of the composite powder, silane coupling agent, catalyst and anhydrous ethanol is 10-14:3-4:0.02-0.03:40-50; the silane coupling agent is triethoxyvinylsilane; and the catalyst is dibutyltin dilaurate.
7. The high-toughness composite cable according to claim 1, characterized in that: In step 2, the constant temperature stirring is stirring at 50-60° C. for 10-12 hours; the washing is washing three times with anhydrous ethanol; and the drying is drying at 70-80° C. to constant weight.
8. The high-toughness composite cable according to claim 1, characterized in that: In step three, the mass ratio of the reaction monomer, prefabricated particles, mercaptosuccinic acid, anhydrous ethanol and initiator is 1.0-1.4:12-14:2.6-3.0:50-60:0.10-0.12; the reaction monomer is 3-methoxy-4-hydroxycinnamic acid; the initiator is benzoin dimethyl ether; the stirring and mixing is stirring at a speed of 600-800r / min for 4-5h; the ultraviolet irradiation treatment is ultraviolet irradiation at a speed of 150-180r / min and a wavelength of 365nm for 20-24h; the inert atmosphere is a nitrogen atmosphere; the cleaning is cleaning three times with anhydrous ethanol; and the drying is drying at a temperature of 80°C to constant weight.
9. The high-toughness composite cable according to claim 1, characterized in that: In step 4, the mass ratio of the modified particles, styrene, crosslinking agent, PP and GMA is 14-16: 1.6-1.8: 0.26-0.30: 20-24: 3.2-3.8; the melt extrusion is performed at a speed of 50 rpm and a temperature of 190° C. for 5 min; and the crosslinking agent is diisopropylbenzene peroxide.
10. A method for preparing a high-toughness composite cable according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: mixing polypropylene, organic modified filler and auxiliary agent in an internal mixer, melting and extruding at a temperature of 190-200° C. to obtain a mixture, and melting and extruding the mixture on the surface of a cable body to obtain the mixture.
Citation Information
Patent Citations
Spraying-free polypropylene composite for automobile exterior trims and manufacturing method thereof
CN107033459A
Weak-conductivity polypropylene composite material and preparation method thereof
CN116199968A
High-toughness wear-resistant cable and preparation method thereof
CN119264555A
Method for preparation of organic zinc-carbon nanotube composite catalyst
KR1020180010820A
Cited By
High-performance modified concrete as well as preparation method and application thereof
CN120965241A